Pemeriksaan Glukosa, Kolesterol dan Asam Urat pada Masyarakat Peserta Car Free Day di Balai Pelatihan Kesehatan (Bapelkes) Kota Semarang - Ana Hidayati Mukaromah; Gela Setya Ayu Putri; Nurul Qomariyah; Wijanarko Wijanarko; Pratiwi R. H. Sya’diah (Jurnal Surya Masyarakat, 2020)
Symptoms of a disease can be prevented if routine health checks are done. Health checks can be carried out in public and private laboratories, or free checks conducted by health education institutions through community service activities. The implementation of community service is carried out by lecturers involving students of the Medical Laboratory Science at the Muhammadiyah University of Semarang. This community service activity was carried out on December 15, 2019 in front of the Semarang Health Training Center Office on December 15, 2019. The inspection method uses Point of Care testing (POCT). The results of the examination that the number of respondents with cholesterol levels above normal for women more than men, while glucose and uric acid levels above normal in men more than women. The average cholesterol, glucose, and uric acid levels for men were 224.2; 123.1; 4.8 mg/dL respectively, while for women is 194.5; 121.2; 6,0 mg/dL. The higher age (12 - 65 years), the average cholesterol level increases from 189 to 217.8 mg/dL (15.25%) and the average glucose level increase from 84.4 to 131.5 mg / dL (55.80%), while the average uric acid level decreases from 5.4 to 5.2 mg / dL (3.85%). The conclusions of the health inspection activity about the result of cholesterol, glucose, and uric acid levels can be used to check public health